Korean Red Ginseng Extract inhibits Tumor Necrosis Factor-alpha-induced Monocyte Adhesion in the Human Endothelial Cells - Hee Kyoung Joo; Sang Ki Lee; Hyo Shin Kim; Yun Jeong Song; Gun Kang; Jin Bong Park; Kwon Ho Lee; Eun Jung Cho; Jae-Hwan Lee; In-Whan Seong; Se Hoon Kim; Chung-Hyun Cho; et al. (Journal of ginseng research, 2008)
Vascular inflammation is an important step in the development of cardiovascular disorder. Since it has not been known whether Korean red ginseng has a role to play on the vascular inflammation, we investigated the effects of Korean red ginseng extract (KRGE) on monocyte adhesion and its underlying signaling mechanism. Monocyte adhesion assay and Western blot were conducted on the human umbilical vein endothelial cells to study monocyte adhesion and the expression of adhesion molecules. Intracellular calcium was measured with Fura-2 fluorescent staining, and superoxide production was measured with lucigenin chemiluminescence in the endothelial cells. KRGE inhibits tumor necrosis factor (TNF)-alpha-induced monocyte adhesion on the endothelial cells at the range of 0.03~1 mg/ml. TNF-alpha-induced vascular cell adhesion molecule-1 and intercellular cell adhesion molecule-1 expression were inhibited by the pretreatment of KRGE in the endothelial cells. KRGE also inhibits TNF-alpha-induced intracellular calcium and the superoxide production in the endothelial cells. This study first demonstrated that KRGE inhibits TNF-alpha-induced monocyte adhesion by inhibiting the adhesion molecule expression, intracellular calcium and superoxide production in the endothelial cells. Therefore, the anti-inflammatory function of KRGE may be contributed to protecting the endothelial dysfunction in the vascular inflammatory disorders. KCI Citation Count: 3